A. 6
B. 5
C. 4
D. 0
D
ĐK: \(x \ne 0.\)
Ta có \({\log _4}{x^2} - {\log _2}3 = 1 \Leftrightarrow {\log _{{2^2}}}{x^2} - {\log _2}3 = 1 \Leftrightarrow {\log _2}\left| x \right| - {\log _2}3 = 1\)
\( \Leftrightarrow {\log _2}\frac{{\left| x \right|}}{3} = 1 \Leftrightarrow \frac{{\left| x \right|}}{3} = 2 \Leftrightarrow \left| x \right| = 6 \Leftrightarrow \left[ \begin{array}{l}
x = 6\\
x = - 6
\end{array} \right.\) (thỏa mãn)
Tổng các nghiệm của phương trình là 6 + (-6) = 0.
Chú ý: \({\log _a}{x^2} = {\log _a}\left| x \right|.\)
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247